Belowground Structural Attributes and Morpho-Anatomical Response Strategies of Bromus valdivianus Phil and Lolium perenne L to Soil Water Restriction - Zhang Y; García-Favre J; Hu H; López IF; Ordóñez IP; Cartmill AD; Symonds V; Kemp PD (MDPI (Basel, Switzerland), 2025)
The effect of soil water restriction on the root structure and morpho-anatomical attributes of Lolium perenne L. (Lp) and Bromus valdivianus Phil. (Bv) was investigated. The anatomical structure of roots from plants grown under two water restriction conditions (20–25% and 80–85% field capacity (FC)) were assessed using paraffin embedding and thin sections. These sections were examined to assess anatomical traits, including root diameter (root D), stele diameter (stele D) and cortex thickness (cortex T), and xylem vessel of Lp and Bv roots. Tiller population, shoot herbage mass, and the shoot-to-root ratio were also determined. Under water restriction, biomass and tillers were significantly decreased (p < 0.001), while the root-to-shoot ratio significantly increased, indicating a higher proportion of Bv roots than shoots when compared to Lp. The root D and stele D, and cortex T, were larger in Bv than in Lp (p < 0.001), indicating a greater adaptation of Bv for water uptake and storage compared to Lp. Xylem vessels were wider in Lp when compared to Bv (p < 0.01), indicating greater water flow within the plant. Water restriction generated a decrease in root D, stele D, and cortex T (p < 0.01). Canonical variate analysis showed that the pith cell wall had a strong positive relationship with water restriction in both Bv and Lp; lignified xylem and the endodermis wall had a close relationship with Lp under water restriction. The findings demonstrate that Lp and Bv have individual structural and morpho-anatomical response strategies to increasing water restriction.
Keywords: drought; pasture brome; perennial ryegrass; root morphology